Exploring the disintermediation effect of blockchain technology on the tourism industry - Faker, Imaan (Department of Information Systems, 2024)
Researchers and practitioners believe that blockchain technology (BCT) will have a substantial impact on all industries, including the tourism industry. Blockchain technology is open-source software that allows the creation of an immutable, distributed ledger (record of transactions). One of the immediate effects recognized by researchers in this domain is that blockchain technology has the potential to remove intermediaries such as Online Travel Agencies (OTA's) and Global Distribution Systems (GDS), thereby disrupting the industry as it stands. This is known as the disintermediation effect. This domain is largely regarded to be in its infancy at both practical and academic levels, hence several researchers are calling for a more systematic and rigorous approach to have a big impact on the development process of this technology for the tourism industry. To address this request, this qualitative study explores disintermediation as a core characteristic and effect of applying blockchain technology to the travel industry. This research aims to strengthen already scarce research in this domain, and thereby move forward blockchain tourism research. It employs a case study design guided by a blockchain-based framework which specifies five factors necessary for an increased level of disintermediation. A modified version of the framework is presented as findings reveal that intermediaries are becoming more innovative in entering the blockchain market, and therefore further sub-factors can be identified based on how disintermediation is currently being introduced in this industry. Keywords: blockchain technology; travel and tourism; disintermediation; intermediaries; online travel.